A brief review of safe management of Covid-19 related death and its control strategies - Chng, Kay Ly; Abdullah, Nor Zamzila; Puteri Nurin Sabrina Binti Mohamad Sabri, Puteri Nurin Sabrina; Shaharin, Sharafina (IIUM Press, 2023)
Coronavirus disease 2019 (COVID-19) is a disease caused by a virus named Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). With the increasing COVID-19 associated deaths, the infectivity and handling of the dead bodies associated with COVID -19 has become a worldwide concern in terms of spreading the infection further during handling of these bodies. As a precaution, measures should be undertaken to contain the spread of infection while handling COVID-19 associated deaths. This article reviews the current management of COVID-19 associated deaths and control strategies in various countries in order to guide medical examiners to handle the bodies including those autopsied.